Osteoinductive Electrospun Scaffold Based on PCL-Col as a Regenerative Therapy for Peri-Implantitis - Claudia Sanhueza; Jeyson Hermosilla; Catherine Klein; Alejandra Chaparro; Iván Valdivia-Gandur; Víctor Beltrán; Francisca Acevedo (MDPI AG, 2023)
Peri-implantitis is a serious condition affecting dental implants that can lead to implant failure and loss of osteointegration if is not diagnosed and treated promptly. Therefore, the development of new materials and approaches to treat this condition is of great interest. In this study, we aimed to develop an electrospun scaffold composed of polycaprolactone (PCL) microfibers loaded with cholecalciferol (Col), which has been shown to promote bone tissue regeneration. The physical and chemical properties of the scaffold were characterized, and its ability to support the attachment and proliferation of MG-63 osteoblast-like cells was evaluated. Our results showed that the electrospun PCL-Col scaffold had a highly porous structure and good mechanical properties. The resulting scaffolds had an average fiber diameter of 2-9 μm and high elongation at break (near six-fold under dry conditions) and elasticity (Young modulus between 0.9 and 9 MPa under dry conditions). Furthermore, the Col-loaded scaffold was found to decrease cell proliferation when the Col content in the scaffolds increased. However, cytotoxicity analysis proved that the PCL scaffold on its own releases more lactate dehydrogenase into the medium than the scaffold containing Col at lower concentrations (PCL-Col A, PCL-Col B, and PCL-Col C). Additionally, the Col-loaded scaffold was shown to effectively promote the expression of alkaline phosphatase and additionally increase the calcium fixation in MG-63 cells. Our findings suggest that the electrospun membrane loaded with Col can potentially treat peri-implantitis by promoting bone formation. However, further studies are needed to assess the efficacy and safety of this membrane in vivo.